Analisis Penerapan Teknologi dalam Pembelajaran dan Dampaknya terhadap Hasil Belajar - Ahmad Zain Sarnoto; Rachmat Hidayat; Lukman Hakim; Khusni Alhan; Windy Dian Sari; Ika Ika (Journal on Education, 2023)
The aim of this research is to analyze the implementation of technology in learning and its impact on student learning outcomes. The method used is a literature study by collecting data from journals and articles related to the implementation of technology in learning. The results show that the use of technology in learning can provide advantages such as increasing the efficiency and effectiveness of learning, facilitating learning skills, and enriching learning content. However, the use of technology also has disadvantages or negative effects such as dependence on technology and potential disruption of concentration. Therefore, the use of technology in learning needs to be managed properly and balanced, as well as developing balanced learning and digital skills for students.